Perspektif Mikro Terhadap Problematika Konversi Lahan di Kawasan Sub DAS Rawas di Kabupaten Musi Rawas Utara Sumatera Selatan - Chuzaimah, Chuzaimah; Sjarkowi, Fahrurozi; Wildayana, Elisa; Yunita, Yunita (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Chuzaimah C, Sjarkowi F, Wildayana E, Yunita Y. 2019. Micro perspectives on land conversion implied problems in rawas sub-watershed in North Musi Rawas District, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 228-235. Palembang: Unsri Press.Â Musi Rawas Utara District is included in the sub-watershed area (watershed) of Rawas, one of the 14 sub-districts included in the Musi River Basin. Factors influencing land conversion, among them are Sporadic Patterned Gradual Conversions where conversion patterns are caused by two main driving factors (economically less productive/beneficial land and the economic urgency of the convert). This paper aims to analyze the factors that influence the occurrence of land conversion from the micro side in the Rawas Sub-watershed area of North Musi Rawas Regency. This research was carried out in Maur Baru Village, Karang Dapo District and Rantau Kadam Village, Karang Dapo District, North Musi Rawas District. Data collected consists of primary and secondary data. The results showed that from the micro aspect there are several factors that influence the occurrence of land conversion: 1) age of plants, where the average rubber farmer who has older rubber plants prefers to do conversion, 2) Land Area, the average farmer who have a small land area prefer to convert their land 3) The number of family dependents, the average farmer who converts has a greater number of dependents than farmers who do not convert, 4) The distance from home to the land, the farmer who converts take the distance from home to the land further than farmers who do not convert land.Keywords: conversion, land, micro